Transabdominal cerclage: preconceptual versus first trimester insertion. (April 2016) - Dawood, Feroza; Farquharson, Roy Gibb
Abstract: Objective: Transabdominal cerclage (TAC) is an effective intervention to prevent spontaneous mid-trimester loss and preterm delivery when a transvaginal cerclage has failed. A TAC may be inserted during the first trimester of pregnancy or preconceptually. The objective of this study was to determine whether or not preconceptual transabdominal cerclage (TAC) confers any benefit over first trimester TAC insertion in terms of associated surgical and pregnancy-related morbidity and subsequent pregnancy outcome. Study design: This was a retrospective and prospective cohort study of 161 consecutive women who underwent preconceptual (PC) TAC versus first trimester (T1) TAC over a 22-year period from January 1993 to January 2015 at a tertiary referral miscarriage clinic. Data was obtained from case note review retrospectively from 1993 to 2006 and prospectively between 2006 and 2015. Inclusion criteria comprised a history of at least one previous spontaneous mid-trimester loss coupled with at least one failed transvaginal cerclage and screening for antiphospholipid syndrome and bacterial vaginosis. Of 144 patients who conceived, 121 had complete pregnancy outcomes; 62 in the preconceptual group and 59 in the first trimester group. Both groups had similar previous pregnancy losses and previous transvaginal cerclage history. Results: Successful pregnancies >24 weeks occurred in 97% of PC TACs compared to 93% in the T1 group. Furthermore, a successful pregnancy >34 weeks occurred in 90% (56/62) in the PC group compared to 74% (44/59) in the T1 group (OR 3.18; CI 1.14–8.8). Significantly fewer patients needed emergency caesarean section for preterm delivery in the PC group (7/62 (12%) versus 21/59 (36%); OR 4.34; CI 1.68–11.32). All 6 failures before 24 weeks gestation (T1 = 4, PC = 2) were associated with antiphospholipid syndrome or bacterial vaginosis. In the T1 group 3/65 (5%) of patients suffered serious surgical complications and haemorrhage >500 mls occurred in 32/65(50%) of cases whereas no surgical complications occurred in the PC group. Conclusions: Preconceptual TAC is more successful in preventing repeat spontaneous mid-trimester loss and preterm labour, and is associated with less surgical and pregnancy-related morbidity compared to first trimester TAC insertion.